Genetic liability to psychiatric disorders in early childhood : phenotypic effects and differing sensitivity to environmental influences - Liuhanen, Johanna (Helsingin yliopisto, 2024)
The large genome-wide association studies conducted during the past fifteen years have broadly increased our understanding of the genetic basis of psychiatric disorders. These studies have shown that not only are all psychiatric disorders highly polygenic, but the implicated genetic factors are largely common variation that all of us carry. This raises the question of whether the common genetic liability is also manifested in the unaffected general population, and, whether they have detectable effects, or phenotypic effects, already in childhood, suggesting genetically influenced psychopathological developmental pathways. Furthermore, the genetic factors may have indirect effects by affecting the sensitivity to the environment. Studying these effects may increase our understanding of genetically influenced developmental pathways to mental health problems, which is essential in considering preventive measures and interventions. The main aim of this thesis was to examine the effect of genetic liability for psychiatric disorders on childhood development and on the sensitivity to environmental influences in the first two years of life. The focus was on the genetic liability for two phenotypes: schizophrenia, a severe mental disorder profoundly affecting the function of neuronal networks and typically manifesting with cognitive impairments, and neuroticism, a trait associated with problems in emotion regulation and general susceptibility to mental health problems. The childhood phenotypes covered a wide range of indicators, from markers of neurophysiological maturation to motor as well as socio-emotional development. The study utilized three Finnish birth cohorts, the Northern Finland Birth Cohort 1966 (Study I), CHILD-SLEEP (Studies II and III), and FinnBrain (Study III). Additionally, a Finnish schizophrenia family sample was used as a replication sample (Study I). Polysomnography recordings analyzed in Study II were available for a subsample (N = 92) of the CHILD-SLEEP birth cohort. Motor development (Study II) ...